Molecular cloning, characterization and gene expression of an antioxidant enzyme catalase (MrCat) from Macrobrachium rosenbergii - Arockiaraj, J.; Easwvaran, S.; Vanaraja, P.; Singh, A.; Othman, R.Y.; Bhassu, S. (Elsevier, 2012)
In this study, we reported a full length of catalase gene (designated as MrCat), identified from the transcriptome database of freshwater prawn Macrobrachium rosenbergii. The complete gene sequence of the MrCat is 2504 base pairs in length, and encodes 516 amino acids. The MrCat protein contains three domains such as catalase 1 (catalase proximal heme-ligand signature) at 350-358, catalase 2 (catalase proximal active site signature) at 60-76 and catalase 3 (catalase family profile) at 20-499. The mRNA expressions of MrCat in healthy and the infectious hypodermal and hematopoietic necrosis virus (IHHNV) challenged M. rosenbergii were examined using quantitative real time polymerase chain reaction (qRT-PCR). The MrCat is highly expressed in digestive tract and all the other tissues (walking leg, gills, muscle, hemocyte, hepatopancreas, pleopods, brain and eye stalk) of M. rosenbergii taken for analysis. The expression is strongly up-regulated in digestive tract after IHHNV challenge. To understand its biological activity, the recombinant MrCat gene was constructed and expressed in Escherichia coli BL21 (DE3). The recombinant MrCat existed in high thermal stability and broad spectrum of pH, which showed over 95% enzyme activity between pH 5 and 10.5, and was stable from 40 °C to 70 °C, and exhibited 85-100% enzyme activity from 30 °C to 40 °C.